Hepatoprotective Effect of Matricaria chamomilla.L in Paraquat Induced Rat Liver Injury - Tavakol, H. S.; Farzad, K.; Fariba, M.; Abdolkarim, C.; Hassan, G.; Seyed-Mostafa, H. Z.; Akram, R. (Drug Research, 2015)
Paraquat (PQ), an effective and widely used herbicide, has been proven to be safe when appropriately applied to eliminate weeds. However, PQ poisoning is an extremely frustrating clinical condition with a high mortality and with a lack of effective treatments in humans. PQ is known to induce injury via a redox cyclic reaction. The purpose of this study was to investigate the effect of aqueous extract Matricaria chamomilla.L (M. chamomilla) against PQ-induced liver injury in association with its antioxidant activity.The male rats were treated by gastric gavage daily with PQ (5 mg/kg/day) and M. chamomilla (50 mg/kg/day) were administered alone or in combination for 7 days. After treatments, total antioxidant capacity (TAC), total thiol molecules (TTG) levels and catalase (CAT) activity in liver tissue were measured. At the end of the experiment, plasma and lung tissue of the animals was separated. The activity of enzymatic scavengers such as CAT, TAC and TTG were measured in liver homogenate.In this sample, the TAC and TTG were lower in the PQ group as compared with control group. Co-administration of PQ with M. chamomilla extract increased TAC and TTG in liver tissue as compared with PQ group.In conclusion, M. chamomilla as natural antioxidant may be considered beneficial for the protection oxidative liver injury in PQ poisoning.
Keywords: paraquat; matricaria chamomilla.L; oxidative stress; liver; rat